Environmental Education in the Studying Curriculums - Othman Braim Hamad; Hataw Kareem Khidir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study focuses on environmental education in the school curriculums. The importance of this research is that it contains good theoretical knowledge about the environmental education, and methods of incorporating environmental topics into educational curriculams, that are the basis for the development of environmental awareness in the education and teaching process. At the practical level, it presents the level of attention and including environmental issues in the school curriculum. The main objective is to determine the level of attention of the KRG education programs towards environmental education. To reach the conclusion, the researchers used the method of content analysis, for this purpose they tried to prepare a list of environmental topics that should be included in the curriculum, then analyzed the content of the seventh-grade curriculum. The conclusion is that the highest level of attention in the curriculam is in the humanrights program, The important thing is that, there is a lower level of the environmental education in the Abilities and Social Values curriculam, but the lowest level is in the Social Subjects curriculam. The highst level among the environmental and its’ issues is the water, but the lawest level is the animals’ issues (poaching, animals are the balance for the environment).. There is afew attention to the practies, activities, and Environmental awareness in the curriculams.